Effect of Auditor Client Tenure, Company Growth, Auditor Reputation, and Leverage of Opinion Audit Going Concern - Nurmala, Putri; Meisnawati, Meisnawati; Thrang, Nguyen Thu (Universitas Pamulang, 2020)
The research objective was to examine and analyze the Influence of Auditor Client Tenure, Company Growth, Auditor Reputation, and Leverage toward Opinion Audit Going Concern. This survey was conducted at Manufacturing Companies registered on the Indonesia Stock Exchange for the period 2013-2017. The data used in this study is secondary data with sampling using purposive sampling method. The data analysis technique used is descriptive technique with a quantitative approach using descriptive statistical tests, multicollinearity test, logistic regression analysis, and coefficient determinant. Based on research has been conducted, the authors note that the auditor client tenure is not effect significantly to the opinion audit going concern, the company growth is not significant influence to opinion audit going concern, auditor reputation has a negative significant effect to opinion audit going concern, and leverage has a significant effect to opinion audit going concern